2017
DOI: 10.18203/2320-1770.ijrcog20172561
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in indication of cesarean section in a tertiary care centre of Central India

Abstract: Background: This study was carried out to find the rate of Cesarean section (CS) in our institute from 2012 to 2016 and also to find any change in the indications of CS over these five years.Methods: A retrospective analysis of data was done from the records of the patients who underwent CS and the rate of Cesarean section and the indications were noticed.Results: The rate of Cesarean section has increased from 43.85% in 2012 to 48.18% in 2016. There is increase in the number of Primary Cesarean cases from 61.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…Contrast to our study, Patil P et al found that they were multigravidas except in 2016 in which the majority were primigravidas. 11 Contrast to our study and similar to study by Patil et al, Gupta M et al found that maximum no. of caesarean sections were in multiparous females (53.82%).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Contrast to our study, Patil P et al found that they were multigravidas except in 2016 in which the majority were primigravidas. 11 Contrast to our study and similar to study by Patil et al, Gupta M et al found that maximum no. of caesarean sections were in multiparous females (53.82%).…”
Section: Discussioncontrasting
confidence: 78%
“…So younger patients were seen in their study. 11 In our study, 68 (68%) patients were primigravida while 32 (32%) patients were multigravida. Contrast to our study, Patil P et al found that they were multigravidas except in 2016 in which the majority were primigravidas.…”
Section: Discussionmentioning
confidence: 45%
“…10 Patil P et al in their study also reported 71.1% emergency caesarean section and 28.9% elective caesarean section. 11 Dasari et al, also reported emergency caesarean section rate of 62.5% which is higher than elective caesarean section rate of 37.5%. 12 In our study we observed that, among cases that 70% of first time mothers underwent emergency caesareans and 25% had elective primary caesareans and it was 75% and 30% respectively in a similar study in Karnataka.…”
Section: Discussionmentioning
confidence: 92%
“…Patil P et al in their study also reported 71.1% emergency cesarean section and 28.9% elective cesarean section. 16 Gayathry D et al also reported emergency cesarean section rate of 62.5% which is higher than elective cesarean section in 37.5%. 17 In our study we observed that, among cases that underwent cesarean section, 68.1% patients underwent primary cesarean section and 67 (31.9%) underwent repeat cesarean section.…”
Section: Discussionmentioning
confidence: 92%